Bearing capacity of embedded channel-shaped steel connections at precast concrete beam end. (15th November 2018) - Guo, Xiaonong; Gao, Shuyu; Wang, Li; Bui, Tien Ngoc
Highlights: A new connection named ECS connection at precast concrete beam end was developed. Static bearing capacity experiments on twelve ECS connections were conducted. The ultimate load of the ECS connection was investigated by parametric studies. The optimum design of the ECS connection was proposed. Abstract: Embedded channel-shaped steel (ECS) connection at precast concrete beam-end proposed in this paper is a kind of novel connection. To study the performance of ECS connection, experiments on 12 specimens were carried out. The embedded length of the ECS, the stirrup spacing, the cavity in the mid-span of the beam and the eccentricity of the ECS were taken into account. Two kinds of failure modes were observed: lever-out of ECS and crushing of the beam-end concrete. The experimental results indicate the following: (1) as the length of ECS increases, the bearing capacity of the ECS connection increases; (2) the stirrup densification could significantly improve the bearing and deformation capacity; (3) the mid-span cavity of the beam has limited influence on the bearing and deformation capacity of the connection; (4) the eccentricity of ECS could slightly reduce the bearing capacity owing to the additional torsion. Subsequently, finite element (FE) models were developed using ABAQUS and validated by the test results. The FE simulations show good agreement with the test results. Based on the verified FE models, a parametric study was conducted, considering different ECS properties including embedded length, section and eccentricity, various stirrup spacing at the beam-end, concrete grade and the distance between cavity and ECS. Finally, to prevent the lever-out of ECS, the optimum design of the ECS connection was proposed according to previous discussion.